The Added Value of Bioimpedance Analysis to NT-proBNP in Predicting Short-term outcome in Acute Heart Failure Patients - Putri Annisa Kamila; Mohammad Saifur Rohman; Setyasih Anjarwani; Djanggan Sargowo; Anna Fuji Rahimah; Indra Prasetya; Muhammad Rizki Fadlan; Salvatore Di Somma (Heart Science Journal, 2021)
Background: Acute heart failure (AHF) is a significant clinical problem, which has a high prevalence, mortality, and rehospitalization. Congestion is critical in AHF's pathogenesis, which is also a predictor of mortality and rehospitalization in patients with AHF. Aim: Knowing the effect of adding a %Total body water (TBW) test detected by Bioimpedance Analysis to NT-proBNP as a short-term clinical outside predictor of patients with acute heart failure Method: This research is an analytical observational study using prospective cohort methods. The research was conducted at Dr. Saiful Anwar Malang Hospital in January 2018-July 2019, with research subjects taken consecutively against all AHF patients hospitalized at UD dr.UD dr. Saiful Anwar Malang. The data taken in the form of NT-proBNP value during mission and %TBW before the patient leaves the hospital detected with NICaS examination, then the outside seen is mortality rate and rehospitalization due to AHF within 90 days after exiting the hospital. Results:  This study involved 65 subjects who were 61 years old and the majority male. Non-survivor patients had a higher NYHA class, NT-proBNP, and %TBW predischarge than the survivor group. Based on statistical analysis, we found that NT-proBNP is a good predictor of mortality (HI: AUC 0.74; 95%CI 0.59-0.90) and rehospitalization (HI: AUC 0.88; 95%CI 0.78-0.97). Similarly , %TBW pre-discharge shows good predictors of mortality (HI: AUC 0.72, 95%CI 0.56-0.87) and rehospitalization (HI: AUC 0.83, 95%CI 0.73-0.94). The addition of the %TBW predischarge parameter to NT-proBNP results in the best predictor numbers among the three for both mortality (HI: AUC 0.84; 95%CI 0.72-0.96) and rehospitalization (HI: AUC 0.92; 95%CI 0.85-1.00). Conclusion: The addition of predischarge %TBW examination detected by bioimpedance analysis tool against NT-proBNP increases the predicted value of short-term clinical outpatient in the form of mortality and rehospitalization of acute heart failure patients.Keywords: acute heart failure, NT-proBNP, bioimpedance analysis, total body water